Wajah Budaya dalam Tafsir Nusantara (Studi Analisis pada Tafsir Pase) - Minnatul Maula (Journal on Education, 2024)
Thesymbols of Islam in Aceh are very well preserved as seen in the daily life of the Acehnese people. The maintenance of religious symbols is said to be good and within certain limits believed to be a form of religious practice. This research is expected to achieve the goal of revealing the characteristics and cultural elements in Tafsir Pase, as well as analyzing the contextualization of the interpretation of Tafsir Pase with phenomena that are happening in society. This research was conducted using a qualitative research model, which is research that is general and does not have a certain pattern. The characteristics of Tafsir Pase include the struggle between Islam and local culture in Aceh which is carried out through the translation of the Qur'an into regional languages. Contextualization of the interpretation of Tafsir Pase is seen in various socio-cultural phenomena in Aceh, for example in the meurukon tradition and the peulheuh kaoy tradition. In addition, contextualization is also seen in inter-religious interactions in Aceh.